2012
DOI: 10.1186/ar3758
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of osteoclastogenesis by Notch2/Delta-like 1 and Notch1/Jagged1 axes

Abstract: IntroductionOsteoclastogenesis plays an important role in the bone erosion of rheumatoid arthritis (RA). Recently, Notch receptors have been implicated in the development of osteoclasts. However, the responsible Notch ligands have not been identified yet. This study was undertaken to determine the role of individual Notch receptors and ligands in osteoclastogenesis.MethodsMouse bone marrow-derived macrophages or human peripheral blood monocytes were used as osteoclast precursors and cultured with receptor acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(89 citation statements)
references
References 37 publications
4
85
0
Order By: Relevance
“…DLL3 is a spondylocostal dysplasia/pudgy gene whose mutation may lead to axial skeletal defects and spondylocostal dysostosis [26][27][28]. Similarly, DLL3 has been reported to be a candidate gene that has been implicated in vertebral malformations, while its binding to Notch represents a significant factor in somitogenesis, capable of promoting osteoclastogenesis through Notch2 [29,30]. A key finding of the present study provided evidence suggesting that it is reasonable to estimate that LINC00311 is upregulated in osteoporosis and that DLL3 is a factor affecting osteoporosis largely due to the increased expression levels of a great number of lncRNAs in orthopedic diseases, with many orthopedic diseases shown to be influenced by DLL3.…”
Section: Figure 14mentioning
confidence: 99%
“…DLL3 is a spondylocostal dysplasia/pudgy gene whose mutation may lead to axial skeletal defects and spondylocostal dysostosis [26][27][28]. Similarly, DLL3 has been reported to be a candidate gene that has been implicated in vertebral malformations, while its binding to Notch represents a significant factor in somitogenesis, capable of promoting osteoclastogenesis through Notch2 [29,30]. A key finding of the present study provided evidence suggesting that it is reasonable to estimate that LINC00311 is upregulated in osteoporosis and that DLL3 is a factor affecting osteoporosis largely due to the increased expression levels of a great number of lncRNAs in orthopedic diseases, with many orthopedic diseases shown to be influenced by DLL3.…”
Section: Figure 14mentioning
confidence: 99%
“…The hybridoma cells were prepared as described above, and antibodies that reacted with mouse Notch2-transfected CHO cells, but not with untransfected CHO cells, were screened and cloned. All these mAbs were purified from ascites produced in pristan-primed ICR nude mice by the caprylic acid and ammonium sulphate precipitation method [36][37][38][39] . Two hundred and fifty micrograms of HMJ1-29 or control hamster IgG (UC8-1B9) and 100 mg of HMN1-12 or HMN2-29 were injected intraperitoneally on the indicated days.…”
Section: Methodsmentioning
confidence: 99%
“…NOTCH mediates hypoxia-induced angiogenesis in RA by increasing the function of microvascular endothelial cells (47). Recent studies using DAPT (48) or an anti-mouse Deltalike 1-blocking monoclonal antibody (49) reported that NOTCH inhibition in mice with inflammatory arthritis reduces the severity of inflammation and inhibits osteoclastogenesis. These reports highlight the complexity of NOTCH signaling under normal and pathological conditions.…”
Section: Figurementioning
confidence: 99%